Nephroprotective Potential of Human Albumin Infusion: A Narrative Review - Christian J. Wiedermann; Michael Joannidis (Gastroenterology Research and Practice)
Albumin infusion improves renal function in cirrhosis; however, mechanisms are incompletely understood. In clinical practice, human albumin is used in various intensive care unit indications to deal with a wide range of problems, from volume replacement in hypovolemic shock, or sepsis, to treatment of ascites in patients with liver cirrhosis. Against the background of the results of recent studies on the use of human albumin in septic patients, the importance of the natural colloid in these critically ill patients is being redefined. In addition to the hemodynamic effects of administration of human albumin impacting on sympathetic tone, attention is being paid to other effects in which its pharmacodynamics is associated with the physiological importance of endogenous albumin. The morbidity and mortality data discussed in this paper support the importance of both the hemodynamic and the pharmacological effects of the administration of human albumin in various indications. The contribution that human albumin could make towards the maintenance of renal function in the course and treatment of severe sepsis and cirrhosis of the liver is the subject of this narrative review.